Preparation of Fluorescent Tubulin Binders. Issue 3 (11th March 2013) - Riva, Elena; Mattarella, Martin; Borrelli, Stella; Christodoulou, Michael S.; Cartelli, Daniele; Main, Marcus; Faulkner, Stephen; Sykes, Daniel; Cappelletti, Graziella; Snaith, John S.; Passarella, Daniele
Abstract Invited for this month's cover are the groups of Prof. Daniele Passarella, Prof. Graziella Cappelletti, Dr. Stephen Faulkner and Prof. John S. Snaith based at the Universities of Milano, Oxford and Birmingham. The image shows that a fluorescent tubulin binder could evidence the tubulin/microtubule network.